Improving efficiency of a multistart with interrupted Hooke-and-Jeeves filter search for solving MINLP problems - Fernandes, Florbela P. (2016)
Publicado em: "Computational science and its applications – ICCSA 2016: 16th International Conference, Beijing, China, July 4-7, 2016, Proceedings, Part I". ISBN 978-3-319-42084-4